Pyelonephritis in Pregnancy: modern draining tactics - V. V. Levchenko; Р. P. Morgun (Вестник урологии, 2019)
Many publications in foreign and domestic papers are devoted to pyelonephritis in pregnancy. At the same time, aspects of the upper urinary tract (UUT) drainage, indications / lack of indications, and the duration of UUT drainage during kidney infections in pregnant women are bypassed. Etiological treatment of this pathology is well described in the European Association of Urology guidelines and American Urological Associations guidelines in accordance with the recommendations of the Food and Drug Administration (FDA). However, there are no references to the management of patients with UUT dilatation, associated with pyelonephritis in pregnant women. The Russian Clinical Guidelines for Urology (2018) also contains very brief information on this issue. Thus, each urological clinic of the Russian Federation has formed its own views on the draining tactics for pyelonephritis in pregnant women, which our colleagues have been following for years and decades. This publication presents an analysis of the literature sources focusing on the current state of the problem of pyelonephritis in pregnancy and the «neсessity» of the UUP drainage. It is intended to initiate a review of the established «tradition» and avoid a significant number of catheter and stent-related complications.